Accessibility at University: Inclusive Dialogues as an Institutional Program - Figari, Cecilia A.; Delorenzi, Erica N.; Deza, Rocío; Carrió, Silvia M.; De Cristófano, Miguel A.; Rufino, María P.; Reboiras, Fabiana I. (Revista del Hospital Italiano de Buenos Aires, 2026)
Introduction: in 2023, University identified opportunities to improve the educational inclusion of people with disabilities, aligning with the Convention on the Rights of Persons with Disabilities. Within this framework, we designed Inclusive Dialogue Instances (EDIs) as an institutional mechanism that enables students, teaching teams, and university authorities to manage supports and reasonable accommodations through agreements. This article presents preliminary results from the EDI implementation.Methods:  we used participatory action research with a qualitative approach to study the mechanisms' dynamics and outcomes over 18 months.Results: we organized the results into three main areas: (1) strengthening educational trajectories—most participants made progress, and one graduated; (2) the production of inclusive communication materials and pedagogical guidelines; and (3) teacher training on inclusion. Through dialogic exchanges, we addressed 12 situations, resulting in 14 agreements on supports and reasonable accommodations. These efforts contributed to strengthening participants’ educational trajectories, while also fostering the development of inclusive materials and their gradual integration into teacher training initiatives.Discussion: the dialogic approach of the EDIs encourages the community to review its assumptions and practices, and to gradually transform institutional culture. In this framework, the entire educational community collectively engages in educational inclusion and shares responsibility.Conclusions: this analysis finds ways to strengthen inclusive skills in disability and accessibility at the university and supports adding these perspectives to policies, practices, and culture.
Keywords: academic accessibility; inclusion; higher education; people with disabilities